2012
DOI: 10.1186/1746-4269-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of use and local knowledge of wild edible plant resources in Nepal

Abstract: BackgroundWild edible plants (WEP) provide staple and supplement foods, as well as cash income to local communities, thus favouring food security. However, WEP are largely ignored in land use planning and implementation, economic development, and biodiversity conservation. Moreover, WEP-related traditional knowledge is rapidly eroding. Therefore, we designed this study to fulfill a part of the knowledge gap by providing data on diversity, traditional knowledge, economic potential, and conservation value of WEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
160
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(187 citation statements)
references
References 43 publications
23
160
2
2
Order By: Relevance
“…In many cases, nonfood uses of wild edible plants are also relevant; in particular, additional medicinal properties are strongly linked with wild edibles intake (Abbasi et al 2013a,b,c;Uprety et al 2012). This is also the case in Vietnam, studied by Ogle et al (2003), where they have acknowledged the multifunctionality of wild edible plants.…”
Section: Americasmentioning
confidence: 86%
See 2 more Smart Citations
“…In many cases, nonfood uses of wild edible plants are also relevant; in particular, additional medicinal properties are strongly linked with wild edibles intake (Abbasi et al 2013a,b,c;Uprety et al 2012). This is also the case in Vietnam, studied by Ogle et al (2003), where they have acknowledged the multifunctionality of wild edible plants.…”
Section: Americasmentioning
confidence: 86%
“…However, within other surveys (Kang et al 2014;Li et al 2015Uprety et al 2012, wild edible fruits are the most cited category (see Table 6.1). Schulp et al (2014) estimate that 65 million people in Europe (14% of all EU citizens), mainly living in rural areas, collect wild food occasionally (including game, mushrooms, vascular plants), and at least 100 million Europeans consume wild food.…”
Section: Americasmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that forest supplies a sizable portion of food for rural farming households of Nepal (Ephrosine, 1994;Koirala, 2006;Rijal, 2010Rijal, -2011Subedi & Pandey, 2002). Uprety et al (2012) documented 44 species of edible fruits and 36 species of edible vegetables that local communities in Nepal have identified and are including in their food items, although such traditional knowledge is eroding throughout the country. The case of the Trans-Himalaya is different than that of other places in Nepal that limited availability of edible items due to harsh climatic conditions has reduced the scope of forest food collection in UpperMustang.…”
Section: Land and Forest Resourcesmentioning
confidence: 99%
“…Arguably, some domesticated food plants have low ascorbic acid content and antioxidant activity as compared to the edible wild plants (Legwaila, Mojeremane, Modisa, Mmolotsi & Rampart, 2011). Studies on edible wild plants from other geographical locations around the world largely focus on the proximate and micronutrient content analysis as well as agronomic improvement of wild and semi-wild crop varieties (Uprety et al, 2012). Meanwhile, southern African indigenous knowledge on the value of edible wild plants is rapidly eroding due to limited local scientific evidence to substantiate their benefit to human health.…”
Section: Introductionmentioning
confidence: 99%